Aplikasi Sensor Passive Infra-Red (PIR) untuk Meningkatkan Keselamatan Pekerja pada Mesin-Mesin Produksi Industri - Joni Welman Simatupang; Indra Sucipta; Azis Wibowo; Kuncoro Kuncoro; Yosua Siringoringo (JIE Scientific Journal on Research and Application of Industrial System, 2020)
This research of literature study discusses about the function and application of infrared sensor-based motion detection devices for work safety on industrial cam machinery.This device was designed to assist the industry in preventing the work accidents that occur due to hazardous industrial machinery. The detector uses a PIR (Passive Infra-Red) sensor as a motion detector of the human limbs. On its application, PIR sensor is placed on a specific side of the machine. Then, the system will provide an automatic cut-off alarms on the machine when a person crosses the fabric area that has been detected by the sensor. It was expected that this way will protect the manpower from the occurrence of work accidents which are caused by dangerous industrial machines. With the implementation of this infrared sensor design, the analysis of hazardous machinery is becoming increased so that this infrared sensor based working security system is growing and easier for shaping in many designs.